Aplikasi response surface methodology pada optimalisasi proses direct acidification terhadap karakteristik produk keju lunak dari penggunaan air lemon [Application of response surface methodology to optimize direct acidification using lemon juice process for soft cheese properties] - Winda Septiana; Sukarno Sukarno; Slamet Budijanto (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Lemon juice can be used as an acidifier to separate curd and whey from milk by decreasing the pH until it reaches the isoelectric point. This study observed the effect of lemon juice as a coagulant for soft cheese-making characteristics using direct acidification that variates the temperature point and the level of lemons maturity classify by the fruit-peel color ratio between yellow and green. Response surface methodology was used in this experimental design with 29 total runs by Design Expert 13 software to search for the optimum formula for the soft cheese-making process. The result shows that the optimum formula reached 70% yellow and 30% green lemon-peel color of fruit maturity, several lemon juice concentrations at 5%, 10%, and 15, and the coagulation temperature point at 30 °C. This research showed that there was an effect of using lemon juice as an acid coagulant in the soft cheese-making process based on the concentration added as an acidifying agent on the characteristic results.